PI3K‐p110‐alpha‐subtype signalling mediates survival, proliferation and neurogenesis of cortical progenitor cells via activation of mTORC2. (3rd May 2014) - Wahane, Shalaka Dhanraj; Hellbach, Nicole; Prentzell, Mirja Tamara; Weise, Stefan Christopher; Vezzali, Riccardo; Kreutz, Clemens; Timmer, Jens; Krieglstein, Kerstin; Thedieck, Kathrin; Vogel, Tanja
Abstract Development of the cerebral cortex is controlled by growth factors among which transforming growth factor beta (TGFβ) and insulin‐like growth factor 1 (IGF1) have a central role. The TGFβ‐ and IGF1‐pathways cross‐talk and share signalling molecules, but in the central nervous system putative points of intersection remain unknown. We studied the biological effects and down‐stream molecules of TGFβ and IGF1 in cells derived from the mouse cerebral cortex at two developmental time points, E13.5 and E16.5. IGF1 induces PI3K, AKT and the mammalian target of rapamycin complexes (mTORC1/mTORC2) primarily in E13.5‐derived cells, resulting in proliferation, survival and neuronal differentiation, but has small impact on E16.5‐derived cells. TGFβ has little effect at E13.5. It does not activate the PI3K‐ and mTOR‐signalling network directly, but requires its activity to mediate neuronal differentiation specifically at E16.5. Our data indicate a central role of mTORC2 in survival, proliferation as well as neuronal differentiation of E16.5‐derived cortical cells. mTORC2 promotes these cellular processes and is under control of PI3K‐p110‐alpha signalling. PI3K‐p110‐beta signalling activates mTORC2 in E16.5‐derived cells but it does not influence cell survival, proliferation and differentiation. This finding indicates that different mTORC2 subtypes may be implicated in cortical development and that these subtypes are under control of different PI3K isoforms. <boxed-text content-type="graphic" id="jnc12718-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Within developing cortical cells TGFβ‐ and IGF‐signalling activities are timely separated. TGFβ dominates in E16.5‐derived cells and drives neuronal differentiation. IGF influences survival, proliferation and neuronal differentiation in E13.5‐derived cells. mTORC2‐signalling in E16.5‐derived cells influences survival, proliferation and differentiation, activated through PI3K‐p110‐alpha. PI3K‐p110‐beta‐signalling activates a different mTORC2. Both PI3K/mTORC2‐signalling pathways are required but not directly activated in TGFβ‐mediated neuronal differentiation.